2021
DOI: 10.1111/vde.13006
|View full text |Cite
|
Sign up to set email alerts
|

Oral dexamethasone sodium phosphate solution significantly reduces pruritus and clinical lesions in feline hypersensitivity dermatitis: an open‐label study

Abstract: Background There are no liquid oral glucocorticoids labelled for management of pruritus and clinical lesions of feline hypersensitivity dermatitis (feline HD). Hypothesis First, to demonstrate that dexamethasone sodium phosphate (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL), an intravenous glucocorticoid, can be absorbed by healthy cats when administered orally. Second, to demonstrate the efficacy of orally administered DexSP for reducing pruritus and clinical lesions in patients with feline HD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…This study's primary outcome was the improvement of the cats' pVAS scores, with the secondary outcomes including improvements in their SCORFAD and QoL scores. However, while the pVAS has been adopted for reporting clinical trials in cats, 2 it has only been formally validated for the assessment of dogs with skin disease.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This study's primary outcome was the improvement of the cats' pVAS scores, with the secondary outcomes including improvements in their SCORFAD and QoL scores. However, while the pVAS has been adopted for reporting clinical trials in cats, 2 it has only been formally validated for the assessment of dogs with skin disease.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…4 By contrast, the dosage of DSP solution in our study was 2.5fold lower (0.2 mg/kg), with the study duration being between 21 to 30 days. 2 A single patient in our study developed transient hyperglycaemia and glucosuria, 2 which was interpreted in the letter as a diagnosis of transient diabetes mellitus. The diagnosis of feline diabetes mellitus requires laboratory changes and the presence of classic clinical signs such as polyuria, polydipsia, polyphagia and weight loss.…”
mentioning
confidence: 76%
“…3 There were no clinical signs of congestive heart failure in seven cats receiving oral daily dexamethasone at 0.55 mg/kg for 56 consecutive days. 4 None of the cats in our DSP study 2 showed clinical signs of congestive heart failure or any abnormalities on routine monitoring of heart rate, rhythm and presence of murmurs. However, we agree with Coyner et al that future studies of any glucocorticoid in cats for longer durations should evaluate glucocorticoid-induced cardiac remodelling using echocardiography and simultaneous electrocardiograms.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We read with interest the recent article "Oral dexamethasone sodium phosphate solution significantly reduces pruritus and clinical lesions in feline hypersensitivity dermatitis: an open-label study" by McClintock et al 1 We have been using oral dexamethasone sodium phosphate solution (Dex SP, Henry Schein; Dublin, OH, USA) (4 mg/mL) in atopic cats for several years with good success and were very pleased to see a publication documenting its efficacy. However, we were concerned by the 21 to 30 day duration of the daily dexamethasone dosing.…”
mentioning
confidence: 99%